2015
DOI: 10.31018/jans.v7i2.688
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different levels of customized fertilizer on soil nutrient availability, yield and economics of onion

Abstract: A field experiment was conducted to study the effect of different levels of customized fertilizer (CF) on soil nutrient availability, yield and economics of onion. The results revealed that the significantly highest plant height (57.77cm), stem diameter (6.03cm) and bulb diameter (15.13cm) at the time of harvest, fertilizer use efficiency,bulb yield (22.34 t ha -1 ) and benefit:cost ratio (2.56) of onion were recorded in 100 % recommended dose of NPK through CF in three equal split doses . The significantly hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 12 publications
(8 reference statements)
5
10
0
Order By: Relevance
“…N decomposition, provide acidic compounds, with more available nutrients in the soil ( Rakshit et al, 2015 ). These results were in line with Kamble and Kathmale (2015) in onion. Similarly, in our results S application recorded significant effect on available N and S, while no effect was seen on available P and K ( Table 7 ).…”
Section: Discussionsupporting
confidence: 90%
“…N decomposition, provide acidic compounds, with more available nutrients in the soil ( Rakshit et al, 2015 ). These results were in line with Kamble and Kathmale (2015) in onion. Similarly, in our results S application recorded significant effect on available N and S, while no effect was seen on available P and K ( Table 7 ).…”
Section: Discussionsupporting
confidence: 90%
“…Fresh bulb yield (q ha -1 ) was found highest in S 4 -N 100 P 50 K 50 S 40 (339.6) followed by S 3 -N 100 P 50 K 0 S 40 (316.4) and S 2 -N 100 P 50 K 50 S 0 (282.4) and minimum Fresh bulb yield (q ha -1 ) was recorded in S 1 -N 100 P 50 K 0 S 0 (247.8). Jaggi (2005) and Mishu et al (2013) concluded that application of 40 kg S ha -1 resulted in the highest yield (10.6 t ha -1 ) among the different doses of sulphur in onion where as results were also supported by Dabhi et al (2004) who concluded that application of 30 kg ha -1 of sulphur in form of gypsum recorded the higher values of yield parameters (plant height, number of leaves plant-1, bulb diameter and bulb weight) and highest bulb yield (246.50 q ha -1 ) in onion.The application of 100% recommended dose of fertilizer (100:50:50 N:P 2 O 5 :K 2 0 kg ha -1 ) either two or three splits through CF to onion appears to be improving soil fertility, yield (22.34 t ha -1 ) ,yield contributing character of onion and getting higher net monetary returns (Kamble and Kathmale 2015). Nasreen et al, (2007) also reported that the addition of nitrogen and sulphur fertilizers exerted significant influence on the number of leaves/plant, plant height, diameter of bulb, single bulb weight and yield of onion.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is quite essential to go for usage of slow release and other customized fertilizers to improve yield and productivity of rice and other crops (Carlier et al 2008;Dahiya et al 2004). Split application of CF in two and three doses in onion increased nutrient availability and ultimately increased bulb yield of onion (Kamble and Kathmale, 2015).…”
Section: Customized Fertilizer a Holistic Crop Nutrition Solutionmentioning
confidence: 98%
“…Nevertheless, grain yield improved by 35 % from 2138 to 3279 kg ha -1 and straw yield by 32 % from 3102 to 4510 kg ha -1 (Mudalagiriyappa et al, 2015). The application of 100% recommended dose of fertilizer (100:50:50 N: P 2 O 5 : K 2 0 kg ha -1 ) either in two or three splits through CF to onion improved soil fertility, bulb yield and yield contributing characters besides providing higher net monetary returns (Kamble and Kathmale, 2015).…”
Section: Role Of Customized Fertilizer On Yield Parameters Of Cropsmentioning
confidence: 98%
See 1 more Smart Citation